Pola Penggunaan Obat Bahan Alam Sebagai Terapi Komplementer pada Pasien Hipertensi Di Puskesmas - Swandari Paramita; Ronny Isnuwardana; Muhammad Khairul Nuryanto; Ruth Djalung; Dewi Guntar Rachmawatiningtyas; Prilandy Jayastri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2017)
Hypertension is a major health problem throughout the world, including Indonesia. The use of traditional medicine as part of the treatment of hypertension is increasing in the last decade. This is due to several factors, especially traditional medicine is a cheaper alternative with fewer undesirable side effects. This study tried to look at the pattern of use of natural medicine as a complementary therapy in hypertensive patients at the health center. The study is a descriptive study conducted in Puskesmas Sempaja Samarinda in the period September 2016, interviewing 62 hypertension patients with the use of natural medicine. The results showed 70.9% of patients with hypertension in the health center also uses natural medicines. All patients using herbal medicine which in theory is proven to lower blood pressure. However, there is no natural medicines used include standardized herbal medicine or phytopharmacy. Only 15.2% of patients using herbal medicine in accordance with the criteria BPOM regulation on herbal medicine. For conclusions, this study shows the patients still need to be educated for the use of natural medicine in the management of hypertension.